2018
DOI: 10.1590/0100-3984.2017.0133
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary inhalation-perfusion scintigraphy in the evaluation of bronchoscopic treatment of bronchopleural fistula

Abstract: ObjectiveTo evaluate the use of pulmonary inhalation-perfusion scintigraphy as an alternative method of investigation and follow-up in patients with bronchopleural fistula (BPF).Materials and MethodsNine patients with BPFs were treated through the off-label use of a transcatheter atrial septal defect occluder, placed endoscopically, and were followed with pulmonary inhalation-perfusion scintigraphy, involving inhalation, via a nebulizer, of 900-1300 MBq (25-35 mCi) of technetium-99m-labeled diethylenetriaminep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…202 e) Confirmar a presença de fístula broncopleural. [203][204][205] f) Avaliar distúrbios pulmonares crônicos parenquimatosos como a fibrose cística; 206,207 g) Avaliar TEP como causa de hipertensão pulmonar. 208 Considera-se como positivo para TEP: 189 • Discordância entre os estudos de ventilação ou inalação, e o estudo de perfusão em pelo menos um segmento ou dois subsegmentos, com hipocaptação presente apenas ou mais extensa na perfusão em contraste com inalação normal (mismatch), respeitando a estrutura pulmonar vascular (hipoperfusão com padrão em cunha e projetada a partir do centro até a periferia pulmonar).…”
Section: Introductionunclassified
“…202 e) Confirmar a presença de fístula broncopleural. [203][204][205] f) Avaliar distúrbios pulmonares crônicos parenquimatosos como a fibrose cística; 206,207 g) Avaliar TEP como causa de hipertensão pulmonar. 208 Considera-se como positivo para TEP: 189 • Discordância entre os estudos de ventilação ou inalação, e o estudo de perfusão em pelo menos um segmento ou dois subsegmentos, com hipocaptação presente apenas ou mais extensa na perfusão em contraste com inalação normal (mismatch), respeitando a estrutura pulmonar vascular (hipoperfusão com padrão em cunha e projetada a partir do centro até a periferia pulmonar).…”
Section: Introductionunclassified
“…A number of recent studies conducted in Brazil have emphasized the importance of nuclear medicine, especially 18 F-FDG-PET/CT, for the diagnosis and follow-up of various illnesses (14)(15)(16)(17)(18) . The present study showed how 18 F-FDG-PET/CT can aid clinicians during the decisionmaking process in cases of SPN with an intermediate probability of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…positive expiratory pressure device, on the aerosol performance of lung deposition [97,[100][101][102][103][104][105]. Other studies with 99m Tc-DTPA focus on distinguishing different lung diseases [74,106,107], understanding the physiology of lung disease [108], and investigating the new application of ventilation scintigraphy [109].…”
Section: Nebulisationmentioning
confidence: 99%